Anthropic rodent populations (Rodentia: Muridae) and their relationship with the environment in an university city of Lima, Perú - Macedo-Bedoya, Jehoshua (2024)
This study examines the populations of anthropic rodents of the Muridae family at the Universidad Nacional Mayor de San Marcos (UNMSM), Lima, Peru with the aim of identifying the species present and their relationship with the environment. Twenty individuals were captured, distributed in Mus musculus (Linnaeus, 1758) (85%), Rattus rattus (Linnaeus, 1758) (10%) and Rattus norvegicus (Berkenhout, 1769) (5%). The 60% were males, 5% females, and 35% were not identified due to their escape. Two areas were analyzed: "Green area behind the dining room" and "Area adjacent to the Huaca (archaeological site)", where M. musculus predominated in both. The analysis of the feces revealed plant remains, animal remains and plastics; while the evaluation of the environmental components showed that different plant families influence the presence of rodents. The results suggest that environmental components and diet are interrelated, and that traps present limitations in the initial capture.